Will human beings be superseded by generative pre-trained transformer 3 (GPT-3) in programming? - Muminov Ibrokhim Botir Ugli (Research Parks Publishing LLC, 2020)
In today’s world, which is full of innovations in various fields, the role of Information Technologies (IT) has increased substantially. Consequently, a mountainous number of independent software engineers as well as IT companies are working together in order to pave the way for the further developments in the IT world. There were a significant number of new technological advancements which have solved dozens of both virtual and real-world issues and have eased the burden from people’s shoulders. As a very conspicuous example would be Generative Pre-trained Transformer 3 or GPT-3 which was introduced in May 2020 as a part of a trend in natural language processing (NLP) systems of pre-trained language representations. This article will provide background data related to GPT-3, its applications in today’s world, positives and negatives, and the future of this remarkable, yet unpredictable tool.